Effects of sarpogrelate on microvascular complications with type diabetes - Yoo, Hyunju; Park, Inwhee; Kim, Dae Jung; Lee, Sukhyang (International Journal of Clinical Pharmacy, 2019)
Background Diabetes is a major cause of microvascular complications. Renin–angiotensin–aldosterone blockers have been known to have the benefits of delaying onset and progression of diabetic complications including nephropathy. Objective To evaluate the effect of sarpogrelate, an antiplatelet agent, on the new onset diabetic complications in patients with type 2 diabetes mellitus. Setting A 1108-bed tertiary university hospital in Korea. Methods A retrospective cohort study was conducted using electronic medical records between 2010 and 2015 in Korea. The study cohort of the propensity score matched patients with or without sarpogrelate was evaluated for the diabetic complications identified with the diagnosis codes in T2DM patients on the metformin based antidiabetic therapy. Nephropathy was further evaluated for progression of kidney function. Main outcome measure The incidence of composite microvascular complications included nephropathy, neuropathy, and retinopathy. Results The 1:2 propensity score matched 478 out of 14,440 patients were included in the final analysis with or without sarpogrelate (162 vs. 316 patients). The incidence of nephropathy, neuropathy, and retinopathy was 1.23% versus 5.38% (HR 0.21, 95% CI 0.05–0.92), 1.23% versus 4.43% (HR 0.26, 95% CI 0.06–1.14), and 6.17% versus 6.33% (HR 0.93, 95% CI 0.43–1.97) with sarpogrelate and without sarpogrelate, respectively. Changes in the estimated glomerular filtration rate and urine albumin creatinine ratio were not significantly different between the groups. Conclusion In Korean patients, sarpogrelate, an antiplatelet agent, was associated with reducing the incidence and progression of nephropathyin type 2 diabetes, but not associated with the composite endpoints including neuropathy and retinopathy.
Keywords: Aged; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Diabetic Nephropathies; Diabetic Neuropathies; Diabetic Retinopathy; Electronic Health Records; Female; Hospitals, University; Humans; Male; Middle Aged; Republic of Korea; Retrospective Studies; Succinates; Diabetic complications; Korea; Nephropathy; Neuropathy; Retinopathy; Sarpogrelate